OPTIMIZING PUBLIC COMMUNICATION IN THE DIGITAL ERA: CHALLENGES AND SOLUTIONS - Novianty Elizabeth Ayuna (AKSELERASI: Jurnal Ilmiah Nasional, 2025)
The rapid digital transformation has shifted public communication patterns from one-way to interactive and real-time. However, this transition brings complex challenges that have the potential to distort public institutions' messages. This study aims to analyze contemporary challenges in digital public communication and formulate effective optimization strategies. The research method used is a descriptive qualitative approach with a literature review (secondary data), which examines various scientific journals, digital trend reports, and related policy documents. The results identify five key challenges: the rapid spread of hoaxes, the vulnerability of online reputation management, the gap in digital literacy, the risk of citizen data security, and polarization caused by echo chamber algorithms. As a solution, this study offers an integrative strategy that includes the participatory use of new media, strengthening rapid fact-checking systems, cross-sector collaboration, and increasing public digital literacy. Furthermore, it emphasizes the importance of empathetic communication using inclusive language to rebuild public trust. The study's conclusions indicate that optimizing public communication involves more than just digitalizing tools, but also transforming communication culture to be more transparent, secure, and humane in order to address the dynamics of information disruption.